El impacto del Programa Juntos en la desnutrición crónica infantil en La Libertad periodo 2014-2017 - Torres Solano, Betsabe (2019)
This thesis was developed with the general objective of determining the impact of the Together program on child chronic malnutrition in La Libertad period 2014 - 2017. The type of research is non-experimental, the design is correlational of longitudinal cut. The population is made up of 3295 children located in the La Libertad region according to ENDES in the 2014-2017 period and a sample of 2749 children located in the La Libertad region was statistically determined. The instrumental variables method has been used, in addition the statistical tests of endogeneity, the F test and the normality test were performed. The endogeneity of the Together program was verified in the first MCO stage, so the instrumental variable of years of education of 25 years and more per district was used for the econometric estimation in the MCO2. The results obtained showed that the Juntos program positively impacts chronic child malnutrition in La Libertad period 2014 - 2017. It was obtained that the number of users of Juntos was 90 users (24.59%) in 2014, 170 users (19.61%) in 2015, 147 users (20.05%) in 2016 and 122 children (15.58%) in 2017 in La Libertad according to ENDES 2014-2017. Child chronic malnutrition still exists based on what is registered by ENDES. For that period in the region it was 19.9% in 2014, 15.9% in 2015, 12.2% in 2015 and 15.6% in 2017.